Success and limiting factors in health service innovation: a theory-generating mixed methods evaluation of UK projects. Issue 5 (25th May 2021) - Leedham-Green, Kathleen; Knight, Alec; Reedy, Gabriel B
Abstract : Objectives: To explore and explain success and limiting factors in UK health service innovation. Design: Mixed methods evaluation of a series of health service innovations involving a survey and interviews, with theory-generating analysis. Setting: The research explored innovations supported by one of the UK's Academic Health Science Networks which provides small grants, awards and structural support to health service innovators including clinical academics, health and social care professionals and third-sector organisations. Participants: All recipients of funding or support 2014–2018 were invited to participate. We analysed survey responses relating to 56 innovation projects. Results: Responses were used to conceptualise success along two axes: value creation for the intended beneficiaries and expansion beyond its original pilot. An analysis of variance between categories of success indicated that participation, motivation and evaluation were critical to value generation; organisational, educational and administrative support were critical to expansion; and leadership and collaborative expertise were critical to both value creation and expansion. Additional limiting factors derived from qualitative responses included difficulties navigating the boundaries and intersections between organisations, professions, sectors and cultures; a lack of support for innovation beyond the start-up phase; a lack of protected time; and staff burn-out and turnover. Conclusions: A nested hierarchy of innovation needs has been derived via an analysis of these factors, providing targeted suggestions to enhance the success of future innovations.